Arsitektur Ergonomi pada Fasilitas Komersil Living World Mall di Denpasar Bali - Frysa Wiriantari; Desak Made Sukma Widiyani (ARCHIHUMANUM, 2023)
Living Word Mall is a commercial facility located on Jalan Gatot Subroto Timur, North Denpasar. Its attractive design invites a lot of people's attention to visit. As a commercial facility that accommodates many users, especially visitors, Living World Mall should apply ergonomic architecture as part of its design. This research will focus on the implementation of ergonomics architecture at the Living World Mall commercial facility in Denpasar Bali in terms of safety, comfort and productivity. These three things will be accompanied by accessibility facilities such as ramps and stairs, space spacing and building health (building physics) which are applied to Living World Mall commercial buildings. This study used descriptive qualitative method. Some of the primary data were obtained from field observations and also the results of interviews with visitors who were active in the mall. Interviews with users were conducted to find out the problems that exist at the research locus to find alternative solutions. The purpose of this research is to examine the use of ergonomic architecture in Living World Mall. The use of qualitative descriptive research methods can be used as a reference in our research because we aim to describe the conditions observed specifically in this area. The results of the study show that the design of Living World Mall has implemented a design that refers to ergonomics for its users. Although there are several parts that need more emphasis primarily related to safety, comfort and productivity factors.